Pemodelan Homologi Protein Receptor Orphan Receptor-1 (ROR-1) Sebagai Target Terapi Chronic Lymphocytic Leukemia (CLL - Ruslin, R; Putri, Suci Rahmawati; Arba, Muhammad (Pharmauho: Jurnal Farmasi, Sains, dan Kesehatan, 2019)
Receptor Orphan Reseptor-1 (ROR-1) is a trans-membrane protein consists of 937 amino acid residues located on 1p31.3 chomosome. ROR-1 has an important role in leukemogenesis of CLL cells. Co-expressions of ROR-1 and TCL enhance leukemogenesis and caused AKT’s phosphorylation, cell’s proliferations, and resistances to apoptosis. This study had done physicochemical characteristics analysis, secondary structure and tertiary structure prediction of ROR-1 Protein using few types of bioinformation tools. The physicochemical characteristics analysis was done by using Expasy Protparam server and the prediction of secondary structure was using Sopma and Psipred. The prediction of ROR-1’s tertiary structure was done by using Modeller 9.19 software  and resulting five ROR-1’s tertiary structures predicted model. The accuration of the results then evaluated using Ramachandran’s plot analysis and it was showed Model 3 is the best models wich percentage is 82%.Keywords: ROR-1, Choronic Lymphocytic Leukemia (CLL), homology modeling, Modeller, Ramachandran plot